Ruthenium based Fischer-Tropsch synthesis on crystallites and clusters of different sizes : from 'Nano" to "Ångstrøm" - Welker, Cathrin Alexandra (Department of Chemical Engineering, 2014)
Includes bibliographical references (p. 137-151).